Getting to the Heart of Low Sensitivity to Alcohol: Context Moderates Low Cardiovascular Response to Alcohol in Persons With a Family History of Alcohol Use Disorder. (17th February 2020) - Bates, Marsha E.; Mun, Eun‐Young; Buckman, Jennifer F.; Vaschillo, Evgeny; Vaschillo, Bronya; Lehrer, Paul; Udo, Tomoko; Lesnewich, Laura M.
Abstract : Background: Low sensitivity to alcohol in persons with a family history of alcoholism (FH+), compared to those without (FH−), contributes to risk for alcohol use disorder (AUD). However, sensitivity of FH+ cardiovascular response to alcohol is not well understood. This gap is significant because cardiovascular processes contribute to emotional regulation and stress response problems theorized to be central to the development and persistence of AUD. This study compared changes in heart rate (HR) and HR variability (HRV) between FH groups after consuming alcohol and control beverages and examined how these changes were moderated by emotional and alcohol‐related contexts. Methods: Young adults ( N = 165) with FH+ ( n = 110) or FH− ( n = 55) each completed 2 sessions, separated by 1 week. They received one of 3 different beverages (alcohol, placebo, and told‐no‐alcohol) in each session. Electrocardiogram data were recorded during pre–beverage consumption and post–beverage consumption baselines, and then during 4 picture cue tasks (neutral, positive, negative, and alcohol‐related). Generalized estimating equations were used to examine differences in cardiovascular reactivity (changes in HR and HRV power at 0.1 Hz) across FH groups, beverage conditions, and picture cue tasks. Results: A significant beverage condition × cue task × FH interaction effect on HRV was observed. The FH+ group, compared to the FH− group, showed (a) significantly less HRV suppression in specific cue contexts following alcohol, (b) a mixed pattern of more and less HRV suppression across cue contexts following placebo, and (c) a similar HRV reactivity pattern in the told‐no‐alcohol condition across cue tasks. For HR, there were no significant effects involving FH. Conclusions: Diminished cardiovascular sensitivity to oral alcohol in FH+ persons varied within a given drinking episode depending on emotional and alcohol‐related features of the context, suggesting that environmental characteristics play a role in the expression of low sensitivity to alcohol among FH+ individuals. Abstract : This study showed that physiological sensitivity to acute alcohol varied within a drinking episode depending on the environment, as did placebo response. Especially in the context of negative emotional and alcohol‐related cues, young adults with a family history of alcoholism, compared to those without, exhibited a low level of cardiovascular response to oral alcohol; this was not observed for neutral cues. Results highlight emotional and appetitive contextual influences on the expression of low sensitivity to alcohol and placebo response.